International Marketing Strategies for Sustainable Development of Enterprises - Tanasiichuk, Alona; Kovalchuk, Svitlana; Nepochatenko, Oleksandr; Froter, Oksana; Kovtun, Eduard; Abdullaieva, Anastasiia (European Journal of Sustainable Development, 2023)
A mechanism for developing and implementing an international marketing strategy for an agricultural enterprise to ensure its sustainable development, a feature of which is to adapt to the new conditions of international markets, is proposed. It is proved that the introduction of a mechanism for developing and implementing an international marketing strategy for an agricultural enterprise will result in a prompt response to changes in the relevant segments of the international market environment through the development and implementation of market research and development activities, preparation of alternative and flexible management solutions aimed at ensuring the sustainable development of the agricultural enterprise. The article develops an approach to identifying suitable markets for the export of the commodity group "1001 Wheat", where there are favorable business conditions for enterprises from Ukraine. The proposed approach is based on the application of global indicators of business conditions in international markets. The foreign markets that demonstrate favorable conditions for doing business in them are identified, which indicates the existence of conditions that are a prerequisite for the formation and implementation of international marketing strategies to ensure the sustainable development of domestic agricultural enterprises producing the "1001 Wheat" product group in the German, Dutch, Belgian, British, Portuguese and Austrian international markets. It is proved that the proposed mechanism for developing and implementing an international marketing strategy for an agricultural enterprise in the postwar period will promote the sustainable development of Ukrainian agricultural enterprises and the recovery of the Ukrainian economy as a whole. Keywords: favorable business conditions, assessment of global indicators, sustainable development strategy, innovative tools for assessing potential markets, markets convergent for the export, sustainable development of enterprises